2018
DOI: 10.1103/physrevb.98.014520
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dirty two-band superconductors with repulsive interband interaction: Normal modes, length scales, vortices, and magnetic response

Abstract: Publisher's PDF Garaud, Julien; Corticelli, Alberto; Silaev, Mikhail; Babaev, Egor Garaud, J., Corticelli, A., Silaev, M., & Babaev, E. (2018) Disorder in two-band superconductors with repulsive interband interaction induces a frustrated competition between the phase-locking preferences of the various potential and kinetic terms. This frustrated interaction can result in the formation of an s + is superconducting state that breaks the time-reversal symmetry. In this paper we study the normal modes and their as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
(119 reference statements)
1
11
0
Order By: Relevance
“…there are no real coherence lengths in general. Note that for dirty isotropic multiband superconductors, the phase difference and density modes can be mixed even without breaking time reversal symmetry [12]. Our findings of the complete mixing of the order parameters and magnetic modes would apply also for that case.…”
Section: Calculation Of Length Scalessupporting
confidence: 52%
See 1 more Smart Citation
“…there are no real coherence lengths in general. Note that for dirty isotropic multiband superconductors, the phase difference and density modes can be mixed even without breaking time reversal symmetry [12]. Our findings of the complete mixing of the order parameters and magnetic modes would apply also for that case.…”
Section: Calculation Of Length Scalessupporting
confidence: 52%
“…These examples shows that accurate coherence length calculations are required while simple estimates can be highly misleading. Calculations of coherence and magnetic field penetration lengths have been made for isotropic multicomponent models for general interactions both in phenomenological and microscopic models [8][9][10][11][12]. The multi-component nature of these systems strongly affects only the coherence lengths, while the magnetic field penetration length is merely renormalized by intercomponent couplings.…”
Section: Introductionmentioning
confidence: 99%
“…1). Although the physics of vortices in, and in the vicinity of, the s + is phase is very rich, it is beyond the scope of the current work and its detailed study will be addressed in a subsequent work [18].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Such configurations arise when domain walls interact with pinning centers or the boundary of the sample [9]. Several proposals were made to distinguish between s + is and s + id states from various configurations of impurities [10][11][12][13][14]. In the most recent proposal [15], it was suggested that for models relevant for Ba 1−x K x Fe 2 As 2 one can distinguish between s + is and s + id superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…However, determining the nature of BTRS states is an extremely difficult task. Proposed experimental signatures are vortex clustering, flux flow viscosity at the BTRS phase transition [14,16], soft collective modes close to the transition [5,6,17,18], formation of Skyrmions [9,19,20], and quasiparticle interference [7,21].…”
Section: Introductionmentioning
confidence: 99%